Evaluation of absolute luxury: Effect of cues, consumers' need for uniqueness, product involvement and product knowledge on expected price. Issue 4 (3rd October 2016) - Bhaduri, Gargi; Stanforth, Nancy
Abstract : Purpose: The purpose of this paper is to investigate the effect of product description cues as a way to differentiate luxury products for the absolute luxury consumer and the effect of individual traits such as need for uniqueness, product involvement, and product knowledge on consumers' perceptions of expected price. Design/methodology/approach: An adult sample of 253 female US consumers were recruited for an online survey. Findings: Consumers' need for uniqueness was related to their level of clothing involvement, which in turn was related to clothing knowledge. Fashion clothing involvement was positively related to participants' product knowledge which in turn positively influenced participants' perceived change in expected price of products in response to various product descriptors or cues related to absolute luxury products. In addition, younger consumers were found to be more involved in fashion clothing than older consumers. Originality/value: This study extends the research into the luxury market and identifies elements of the marketing mix which might be manipulated to better inform potential customers about the luxury product. The study further emphasizes that product descriptors or cues can have an impact on price judgments, especially for highly involved and knowledgeable consumers. This is especially important to academicians as well as marketers since high fashion involved consumers have often been seen as drivers, influential, and legitimists of the fashion adoption process.